Small Medium Enterprises (SMES) in turkey and Malaysia a comparative discussion on issues and challenges - Abdul Razak, Dzuljastri; Abdullah, Moha Asri; Ersoy, Arif (Zes Rokman Resources, 2018)
Small and medium-sized enterprises (SMEs) in Turkey and Malaysia play significant economic and social roles by offering new job opportunities, lowering unemployment rate, increasing competition, productivity and providing substantial benefits to the economy of both countries. It has contributed to more than 90 percent of total establishments and more than 40percent of countries GDP. The purpose of this study is to investigate issues and challenges that have affected the growth of SMEs in both countries. In identifying the issues and challenges, three factors in the Kobayashi (1997) micro model for SMEs namely, financial assistance, impact of knowledge based economy and impact of marketing assistance were analyzed. The methodology employed is by means of secondary data and literature review. This study will contribute to our understanding of the similarities and differences on issues and challenges faced by SMEs in both countries. This will assist policy makers and regulators in taking the remedial steps to improve their performances Keywords: SMEs, Kobayashi,Issues Challenges,Turkey, Malaysia,